Harnessing the paradoxical phenotypes of APOE ?2 and APOE ?4 to identify genetic modifiers in Alzheimer's disease. - Kim, Y.W.; Al-Ramahi, I.; Koire, A.; Wilson, S.J.; Konecki, D.M.; Mota, S.; Soleimani, S.; Botas, J.; Lichtarge, O. (Alzheimer's & dementia, 2021)
The strongest genetic risk factor for idiopathic late-onset Alzheimer's disease (LOAD) is apolipoprotein E (APOE) ?4, while the APOE ?2 allele is protective. However, there are paradoxical APOE ?4 carriers who remain disease-free and APOE ?2 carriers with LOAD. We compared exomes of healthy APOE ?4 carriers and APOE ?2 Alzheimer's disease (AD) patients, prioritizing coding variants based on their predicted functional impact, and identified 216 genes with differential mutational load between these two populations. These candidate genes were significantly dysregulated in LOAD brains, and many modulated tau- or ?42-induced neurodegeneration in Drosophila. Variants in these genes were associated with AD risk, even in APOE ?3 homozygotes, showing robust predictive power for risk stratification. Network analyses revealed involvement of candidate genes in brain cell type-specific pathways including synaptic biology, dendritic spine pruning and inflammation. These potential modifiers of LOAD may constitute novel biomarkers, provide potential therapeutic intervention avenues, and support applying this approach as larger whole exome sequencing cohorts become available.